Comparison of Two Diagnostic Assays for Anti-Laminin 332 Mucous Membrane Pemphigoid - Goletz, Stephanie; Giurdanella, Federica; Holtsche, Maike M.; Nijenhuis, Miranda; Horvath, Barbara; Diercks, Gilles F. H.; Zillikens, Detlef; Hashimoto, Takashi; Schmidt, Enno; Pas, Hendri H. (Frontiers in Immunology, 2021)
Anti-laminin 332 mucous membrane pemphigoid (MMP) is an autoimmune blistering disease characterized by predominant mucosal lesions and autoantibodies against laminin 332. Exact diagnosis of anti-laminin 332 MMP is important since nearly 30% of these patients develop solid cancers. This study compared two independently developed diagnostic indirect immunofluorescence (IF) tests based on recombinant laminin 332 expressed in HEK239 cells (biochip mosaic assay) and the migration trails of cultured keratinocytes rich in laminin 332 (footprint assay). Sera of 54 anti-laminin 332 MMP, 35 non-anti-laminin 332 MMP, and 30 pemphigus vulgaris patients as well as 20 healthy blood donors were analyzed blindly and independently. 52/54 and 54/54 anti-laminin 332 MMP sera were positive in the biochip mosaic and the footprint assay, respectively. In the 35 non-anti-laminin 332 MMP sera, three were positive in both tests and four others showed weak reactivity in the footprint assay. In conclusion, both assays are easy to perform, highly sensitive and specific, which will further facilitate the diagnosis of anti-laminin 332 MMP.